(untitled) (LACCEI, 2024)
The consumption of foods with high contents of anthocyanins, such as blueberry (Vaccinium corymbosum), can help to prevent various diseases due to its antioxidant and anti-inflammatory capacity. Being a perishable product and with considerable non-exportable surpluses, an alternative of use and consumption would be through derivate products, for example, as vinegar. The aim of the research was to evaluate the effect of the application of sugar enrichment in the blueberry-must and application of microwave radiation on the extraction of anthocyanins in the base wine during alcoholic fermentation, as a previous stage for acetification of the vinegar. Among the main results, improvements in the alcoholic degree in the base wines were obtained through sugar enrichment, reaching increases of up to 100% respect to the control wine, while no significant effect of the application of microwave radiation in the extraction of anthocyanins was demonstrated. On the other hand, in the vinegars, reductions in the content of total monomeric anthocyanins (AMT) were obtained with respect to the base wine, up to 69%, which indicates the degradation of anthocyanins during the acetic fermentation. Based on the obtained results, the extraction of anthocyanins can be improved through sugary enrichment prior to alcoholic fermentation, allowing improvements in the anthocyanin content in the vinegar.